Disturbances in Cholesterol Homeostasis and Non-alcoholic Fatty Liver Diseases - Malhotra, Pooja; Gill, Ravinder K.; Saksena, Seema; Alrefai, Waddah A. (Frontiers in Medicine, 2020)
Non-alcoholic fatty liver disease (NAFLD) is a major health problem associated with obesity along with other features of the metabolic syndrome including insulin resistance and dyslipidemia. The accumulation of lipids in hepatocytes causes liver damage and triggers inflammation, fibrosis and cirrhosis. Beside fatty acids and triglycerides, evidence shows an increase in free cholesterol in the liver with subsequent toxic effects contributing to liver damage. The maintenance of cholesterol homeostasis in the body requires a balance between several pathways responsible for cholesterol synthesis, transport and conversion into bile acids. Intestinal absorption is also one of the major determinants of cholesterol homeostasis. The nature of changes in cholesterol homeostasis associated with NAFLD has been a subject for extensive investigations. In this article, we will attempt to provide a brief overview of the current knowledge about disturbances in cholesterol metabolism associated with NAFLD and discuss how certain molecular targets of these pathways could be exploited for the treatment of this multifactorial disease.